Contesting Alinesitoué Diatta: The polyphony of prophetic discourses in Boubacar Boris Diop's Les tambours de la mémoire - Panuntun, Ari Bagus; Istiqomah, Latifa Nasywa Tiara; Arthatiya, Annaya Zahra (LITERA, 2024)
Alinesitoué Diatta is a prophetess within the Awasena religion, an indigenous religion from Casamance, Senegal. However, nowadays, her prophetic identity is less known than her image as a national hero, specifically as a Senegalese freedom fighter. This article examines the representation of Alinesitoué Diatta through the character Johanna Simentho in Boubacar Boris Diop's novel Les Tambours de la Mémoire (1987). It aims to explore whether the novel revives the prophetic narrative of Alinesitoué Diatta or merely continues her political image constructed by the Senegalese government. Moreover, this article analyzes the relation between the character's representation and the narrative contestation about her that occurred in Senegal during 1980s. This research uses Mikhaí¯l Bakhtin's polyphony theory, Stephen Greenblatt's new historicism, and Max Weber's prophetic theory to examine these topics. Employing a descriptive qualitative method, we collected primary data consisting of novel quotations about the character Johanna Simentho and compared them with Alinesitoué Diatta's historical narrative. This research found that the use of polyphonic narratives in the novel represents the narrative contestation over Alinesitoué Diatta by the Senegalese government, FCS, and Kabrousse villagers. Furthermore, the article also found that the novel has revived Alinesitoué Diatta's prophetic narrative even though this prophetic representation intertwines with a masculine narrative depicting her as "Yo jigeen ci mun goor" or "a woman who is stronger than men".